Transnational ties and performance of immigrant firms: evidence from Central Italy. Issue 8 (24th August 2020) - Brzozowski, Jan; Cucculelli, Marco
Abstract : Purpose: The purpose of this study is to analyze the determinants of transnational business ties (i.e. ties with the country of origin) and to investigate their impact on the economic performance of immigrant firms. Design/methodology/approach: Based on the representative survey conducted among 259 foreign-born immigrant entrepreneurs in Marche region (Central Italy), the study investigates the determinants of having transnational ties with countries of origin. Then it compares the effect of transnational ties and the effect of alternative domestic ethnic business ties on the performance of immigrant firms. Findings: This study demonstrates that having transnational ties is more likely for individuals with former entrepreneurial experience in the home countries and with higher education acquired in Italy. The performance of immigrant firms in the 2014–2016 period (measured by the level of revenues) is positively related to transnational ties – this effect is very strong and significant. On the other hand, reliance on the domestic ethnic ties (i.e. ties with co-ethnic population in Italy) is one of the key factors that inhibits further growth of immigrant enterprises. Originality/value: This study advances the understanding of how immigrant entrepreneurs create transnational business ties with their home countries. Additionally, this research contributes to the existing literature on immigrant entrepreneurship, by explaining the role of heterogeneous business ties: transnational connections, domestic ties with co-ethnic partners and ties with individuals from native population (in this case: Italy) for the entrepreneurial performance. Consequently, it offers recommendations for policy-makers willing to encourage entrepreneurial activities of immigrants in host countries and to their counterparts in home countries, who are planning to use the advantage diaspora entrepreneurial potential for the benefit of their economies.